2007
DOI: 10.1073/pnas.0704677104
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of oncogenic properties of c-Myc by LKB1-controlled epithelial organization

Abstract: 3D culture ͉ apoptosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
97
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 27 publications
(36 reference statements)
16
97
0
Order By: Relevance
“…2A). 33 To test whether MYC-induced apoptosis correlates with disturbed lineage-identity under these culture conditions, we treated developing MCF10A acini with 4-OHT. In 2D monolayer culture, more than 80 % of MCF10A cells stain positive for the basal Keratin 14 (K14), while the remaining cells are Keratin 8 (K8, luminal) or double positive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). 33 To test whether MYC-induced apoptosis correlates with disturbed lineage-identity under these culture conditions, we treated developing MCF10A acini with 4-OHT. In 2D monolayer culture, more than 80 % of MCF10A cells stain positive for the basal Keratin 14 (K14), while the remaining cells are Keratin 8 (K8, luminal) or double positive.…”
Section: Resultsmentioning
confidence: 99%
“…7,33 Stable overexpression of MYC or MYC-ER fusion proteins was achieved by transduction with lentiviral pRRL-SFFV vectors and packaging plasmids psPAX2 and pMD2.G (Didier Trono) in the presence of 8 mg/ml protamine sulfate.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedure was previously described ( 46 ) and is provided in the Supplementary Methods.…”
Section: D Culturementioning
confidence: 99%
“…One study-using mammary epithelial cells grown in a 3-dimensional Matrigel culture system-has shown that polarity defects accompanying LKB1 inactivation unmask the oncogenic activity of c-Myc (Partanen et al, 2007). In this system, proliferating cells eventually form into quiescent polarized acinar structures.…”
Section: Mechanisms Of Polarity Controlmentioning
confidence: 99%